2010
DOI: 10.1086/649844
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology, Organization, and Productivity in the Public Sector: Evidence from Police Departments

Abstract: We examine the relationship between information technology (IT), productivity, and organization using a new panel data set of police departments that covers 1987-2003. When considered alone, increases in IT are not associated with reductions in crime rates, increases in clearance rates, or other productivity measures, and computing technology that increases reported crime actually generates the appearance of lower productivity. These results persist across various samples, specifications, and IT measures. IT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 45 publications
3
123
0
3
Order By: Relevance
“…Management practices greatly affect ICT penetration and exploitation, especially in reference to human resource practices (Bloom et al, 2012). In fact, some studies find that it is not investment in ICT per se that raises productivity but rather its complementarity with changes in the organisation structure and different management practices (Garicano and Heaton, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Management practices greatly affect ICT penetration and exploitation, especially in reference to human resource practices (Bloom et al, 2012). In fact, some studies find that it is not investment in ICT per se that raises productivity but rather its complementarity with changes in the organisation structure and different management practices (Garicano and Heaton, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other research has shown that police departments that implement IT have fewer officers per capita (Nunn, 2001), which might indicate greater efficiency. On the other hand, IT might be associated with improved productivity only when coupled with complementary organizational and management practices (Garicano and Heaton, 2010).…”
Section: Technology In the Srtb Contextmentioning
confidence: 99%
“…Over the 1995-2001 period, the matched data-set contains about 840,000 individuals aged 16-64 who were observed in about 1 million job spells (about 3 million job×year observations) at over 23,000 firms. 24 On average 29% of workers in the sample are female, 30% are white collar 21 These data are known as the Company Register database (Registro delle Imprese). Law 580 of 1993 established the Chamber of Commerce as the depository for standardized financial and balance sheet data for all incorporated firms in Italy.…”
Section: Datamentioning
confidence: 99%
“…The two measures are highly correlated (correlation > 0.98), and the median ratio between them is close to 1.0. 24 Firms in the sample represent about 10% of the total universe of firms contained in the VWH. The vast majority of the unmatched firms are non-incorporated, small family business (societa' di persona) that are not required by existing regulations to maintain balance sheets books, and are therefore outside the AIDA reference population.…”
Section: Datamentioning
confidence: 99%